High Performance Enhancement-Mode AlGaN/GaN MIS-HEMT with Selective Fluorine Treatment - Chao Yang; Jiayun Xiong; Jie Wei; Junfeng Wu; Bo Zhang; Xiaorong Luo (Advances in Condensed Matter Physics)
A novel enhancement-mode (E-mode) Metal-Insulator-Semiconductor- (MIS-) HEMT with selective fluorine ion (F−) treatment is proposed and its mechanism is investigated. The HEMT features the Selective F− treatment both in the AlGaN channel region and in the thick passivation layer between the gate and drain (SFCP-MIS-HEMT). First, the F− in the passivation layer not only extends the depletion region and thus enhances the average electric field (E-field) between the gate and drain by the assisted depletion effect but also reduces the E-field peak at the gate end, leading to a higher breakdown voltage (BV). Second, in the AlGaN channel region, the F− region realizes the E-mode and the region without F− maintains a high drain current (ID). Third, MIS structure suppresses the gate leakage current, increasing the gate swing voltage and the BV. Compared with a MIS-HEMT with F− treatment in whole channel (FC-MIS-HEMT), SFCP-MIS-HEMT increases the BV by 46% and the saturation drain current (ID,sat) by 28%.